Efektivitas public relations digital dalam memperkuat brand awareness perbankan syariah di era transformasi digital - Putri, Dieva Rullyeza Chelsealia (Maliki Interdisciplinary Journal, 2025)
The development of digital technology has brought significant changes to the communication patterns of financial institutions, including Islamic banking in Indonesia. This study aims to analyze the effectiveness of digital public relations strategies in increasing brand awareness of Islamic banking in the era of digital transformation. The research method used is a qualitative approach with a literature review of various relevant national journals. The results of the study indicate that the implementation of digital public relations through social media, websites, and online campaign activities has proven effective in increasing public awareness and trust in Islamic banking. Key factors for success include message consistency, two-way interaction with the public, and the reinforcement of Islamic values ​​in every digital communication. Therefore, optimizing digital PR strategies is a strategic step in strengthening the image, reputation, and competitiveness of Islamic banks in the digital era.